THE CORRELATION BETWEEN STUDENTS PERCEPTION AND ACADEMIC PERFORMANCE TOWARDS ONLINE LEARNING SYSTEM DURING COVID-19 PANDEMIC - Achmad Khoiri; Badriyah Ulfah; Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2022)
Online learning is a system based on formal teaching with the help of electronic devices and used internet connection to facilitates more flexible distance learning and a vast network to connect. Online learning has been carried out in universities in the last two years due to the COVID-19 pandemic. This study aims to determine the correlation between students' perceptions and academic performance towards the online learning system during the COVID-19 pandemic of English education study program students at Indo Global Mandiri University Palembang. quantitative method used in this study with a correlational design to analyze the data. The sample was students majoring in English Education intake 2018, 2019, and 2020. Seventy-eight students from three intakes of English Education students participated in this study. The data sources used by the researchers are graphs of student academic performance and a questionnaire. This research shows that student's academic performance is not much impacted by their perception of online learning. Based on Malik and Singh (2016) Academic performance can be influenced by internal and external factors, such as; Motivation, Economics, Social, and Family. Therefore, students, lecturers, and educational institutions must synergize in improving services, communication, and online-based education systems to benefit more from online learning systems.